Associations of Serum Total Homocysteine Levels with Various Demographic, Clinical and Genetic Characteristics in Healthy Greek Adults - Mazokopakis, Elias E; Papadomanolaki, Maria G; Papadakis, John A (Acta medica (Hradec Kralove), 2023)
AIM: The aim of this study was to investigate the association of serum total Hcy (tHcy) levels with various demographic, clinical and genetic characteristics in healthy Greek adults. METHODS: Anthropometric characteristics (height, weight), systolic and diastolic blood pressure, complete blood count and biochemical assessments, were recorded and measured among 383 Greek adults (199 men). Serum folate, Cobalamin (Cbl) and tHcy levels were determined using immunoassays methods. The MTHFR C677T and A1298C gene polymorphisms were genotyped using polymerase chain reaction and reverse hybridization. RESULTS: MTHFR C677T gene polymorphism, serum folate and Cbl levels were correlated with serum tHcy levels independently. The individuals with 677TT genotype had significantly higher serum tHcy levels than individuals with 677 CC or CT genotypes. Regarding the MTHFR C677T gene polymorphism, the existence of the T allele was associated with statistically significantly lower serum folate and higher serum tHcy levels than C allele. Regarding the MTHFR A1298C gene polymorphism, the existence of the C allele was associated with statistically significant lower serum tHcy levels than A allele. Furthermore, there was no significant correlation between the serum tHcy levels and demographic (except age) or clinical characteristics (sex, BMI, smoking status, SBP, DBP, HGB, HCT, TC, TG, HDL-C, LDL-C, TC/HDL-C). CONCLUSIONS: Serum tHcy levels are influenced by the existence of MTHFR C677T gene polymorphism (mainly 677TT genotype), serum folate and Cbl levels. Individuals with hyperhomocysteinemia should be further investigated for the existence of MTHFR C677T gene polymorphism, with the aim to determine the suitable treatment.
Keywords: dospělí; Genotype; Adult; Greece; Folic Acid; lidé; genotyp; kyselina listová; homocystein; Methylenetetrahydrofolate Reductase (NADPH2); Male; polymorfismus genetický; Homocysteine; mužské pohlaví; methylentetrahydrofolátreduktasa (NADPH2); Polymorphism, Genetic; Demography; Řecko; demografie; Humans